2003
DOI: 10.1053/jhep.2003.50219
|View full text |Cite
|
Sign up to set email alerts
|

Triple Therapy With Amantadine in Treatment–Naive Patients With Chronic Hepatitis C: A Placebo–Controlled Trial

Abstract: The antiviral efficacy of amantadine in patients with chronic hepatitis C is controversial. In this randomized, prospective, placebo-controlled, multicenter trial, triple therapy with interferon alfa (IFN-␣)-2a plus ribavirin and amantadine (amantadine group) was compared with combination therapy IFN-␣ plus ribavirin (control group). Four hundred previously untreated patients with histologically proven chronic hepatitis C were randomly allocated to treatment with amantadine sulphate (100 mg twice daily orally)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 38 publications
5
51
1
4
Order By: Relevance
“…In agreement with previous studies, 22 we observed a correlation between the GGT level and the necroinflammation score and fibrosis. GGT elevations caused by toxic injury and obesity are unlikely due to strict inclusion criteria in the present study and a lack of correlation with body mass index.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies, 22 we observed a correlation between the GGT level and the necroinflammation score and fibrosis. GGT elevations caused by toxic injury and obesity are unlikely due to strict inclusion criteria in the present study and a lack of correlation with body mass index.…”
Section: Discussionsupporting
confidence: 93%
“…21,22 Although baseline GGT levels and ALT levels are correlated, the effects on viral kinetic parameters were different in the present study. While patients with persistently normal ALT levels tended to a lower efficacy of blocking virus production and reduced infected cell loss, a lower efficacy of blocking virus production ⑀, a lower infected cell loss ␦, and a lower infected cell loss during treatment m␦ was observed in patients with elevated baseline GGT levels compared with patients with normal baseline GGT levels.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…14,23,24 By antiviral triple therapy containing amantadine, PEG IFN-␣ and ribavirin sustained virological response rates of 25% to 60% were achieved compared with 28% to 44% observed in patients receiving dual combination with PEG IFN-␣ and ribavirin. 11,25,26 A meta-analysis comprising 3257 treatmentnaïve patients enrolled in 17 controlled clinical trials showed that amantadine augments the response to interferon alfa in treatment-naïve patients, albeit to a lesser extent than most clinical trials assumed for sample size calculation. 15 In the largest randomized, placebo-controlled trial, 400 treatment-naïve patients with chronic hepatitis C were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Over more than 10 years, the antiviral efficacy of amantadine in combination with interferon alfa alone or interferon alfa and ribavirin has been evaluated in numerous yet underpowered clinical trials. [9][10][11][12][13][14] Randomized placebo-controlled multicenter clinical trials revealed controversial results for treatment-naïve patients, and meta-analyses suggested a slight improvement of sustained virological response rates for interferon-based treatment with amantadine. 15 In addition to results from clinical trials, in vitro examinations suggested inhibition of the HCV p7-protein by amantadine and an association of specific amino acid variations in the p7-protein with virological response to amantadine in combination with PEG IFN-␣ and ribavirin.…”
mentioning
confidence: 99%